Pengaruh Perbedaan Lama Perendaman Terhadap Maskulinisasi Larva Ikan Guppy ( Poecilia retriculata ) Menggunakan Madu - Moch Bachrul Asal; Achmad Kusyairi; Sumaryam Sumaryam (Universitas Mataram, 2026)
Guppy fish (Poecilia reticulata) hold high commercial value, particularly the males, due to their aesthetic colors and morphology. This study aims to determine the effect of different soaking durations in honey on the masculinization of guppy larvae and to identify the optimal immersion time. This experimental study utilized a Completely Randomized Design (CRD) with 5 treatments and 5 replications, using a honey dosage of 5 ml/L with soaking durations of: 8 hours, 10 hours, 12 hours, 14 hours, and 16 hours. The results showed that the variation in soaking duration had a significant impact on the percentage of masculinization. The 12-hour soaking treatment yielded the best results, achieving a male percentage of 90.1%. Water quality parameters during the 45-day rearing period remained stable within the optimal range, with temperatures of 23.1–26.9°C, pH of 7.0–7.2, and dissolved oxygen (DO) of 6.1–6.7 ppm. In conclusion, the use of honey as a natural ingredient is effective in significantly inducing male sex differentiation in guppy fish larvae.